Infectivity of cysts of the ME-49 Toxoplasma gondii strain in bovine milk and homemade cheese - RM Hiramoto; M Mayrbaurl-Borges; AJ Galisteo Jr; LR Meireles; MS Macre; HF Andrade Jr
OBJECTIVE: Analyze the infectivity and storage resistance of cysts of the ME-49 strain of Toxoplasma gondii in artificially infected bovine milk and homemade fresh cheese. METHODS: Pasteurized bovine milk was infected with 10 cysts/ml of the ME-49 strain of T.gondii and inoculated in different groups of mice, immediately or after storage at 4ºC for 5, 10 and 20 days. Homemade fresh cheese was prepared with artificially infected milk, and also tested in groups of mice, using the same storage process. Infection was identified by the presence of cysts in the brain or serological testing in challenged mice after 5 weeks, confirmed by Western Blot and histology. RESULTS: The infectivity of cysts of the ME-49 strain of T.gondii was maintained in the milk even after storage for 20 days at refrigerator temperatures. Cysts were also able to survive the production process of homemade fresh cheese and storage for a period of 10 days in the same conditions. CONCLUSIONS: These data demonstrated that milk and dairy products could be an important source of T.gondii in human contamination, reinforcing the importance of milk pasteurization before any processing or ingestion.